2013
DOI: 10.1007/s11368-013-0658-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water management on cadmium and arsenic accumulation by rice (Oryza sativa L.) with different metal accumulation capacities

Abstract: Purpose Water management affects the bioavailability of cadmium (Cd) and arsenic (As) in the soil and hence their accumulation in rice grains and grain yields. However, Cd and As show opposite responses to soil water content, but information, particularly on irrigation, is missing on a field scale. The purpose of the present study was therefore to find a water management regime that can lower accumulation of both Cd and As in grain without yield loss. Materials and methods Two rice (Oryza sativa L.) cultivars,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 30 publications
3
47
1
Order By: Relevance
“…Comparatively, intermittent and intermittent-aerobic conditions in pot conditions and the conventional regime (e.g., flooding-intermittent) were suitable for acceptable yields of this cultivar. Furthermore, the responses of As and Cd accumulation in this upland rice cultivar to water management in this study are similar to those of lowland rice cultivars used in previous studies (Hu et al, 2013a(Hu et al, , 2013b. Therefore, it can be speculated that the accumulation of As and Cd in the grains is mainly dependent on elemental availability in the soil as influenced by water management no matter what rice cultivar is grown.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Comparatively, intermittent and intermittent-aerobic conditions in pot conditions and the conventional regime (e.g., flooding-intermittent) were suitable for acceptable yields of this cultivar. Furthermore, the responses of As and Cd accumulation in this upland rice cultivar to water management in this study are similar to those of lowland rice cultivars used in previous studies (Hu et al, 2013a(Hu et al, , 2013b. Therefore, it can be speculated that the accumulation of As and Cd in the grains is mainly dependent on elemental availability in the soil as influenced by water management no matter what rice cultivar is grown.…”
Section: Discussionsupporting
confidence: 84%
“…However, Cd concentrations in straw, husk and brown rice decreased markedly in higher irrigation regimes (flooding and conventional) compared to aerobic and intermittent treatments under field conditions. Thus, irrigation regime merits special attention in the mitigation of metal(loid) accumulation in rice grains when crops are grown in soils with combined pollution by As and Cd (Hu et al, 2013a(Hu et al, , 2013b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flooding conditions prevail during almost the entire cropping period, because lowland rice is extremely sensitive to water shortage (Kögel-Knabner et al, 2010). Flooded paddy soils undergo one or two drainage periods: one at the filling stage to enable faster rice ripening and easier harvesting and sometimes at the tillering stage to control ineffective tillering (Hu et al, 2013). During flooding of paddy soils, the redox potential (Eh) will decrease after the depletion of O 2 and subsequently the following reduction reactions will either sequentially or simultaneously take place: denitrification and transformation of Mn(III/IV) to Mn(II), of Fe(III) to Fe(II), and of SO 4 2 − to HS − (Murase and Kimura, 1997;Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these properties can change with variation in soil moisture content and thus change soil metal availability (Cornu et al 2007). Studies have shown that water management can change soil metal mobility and availability and thus manipulate metal accumulation in rice plants (Yang et al 2009;Hu et al 2013;Xu et al 2013). However, the effects of soil drying during wetting-drying cycles on metal availability have received little consideration in these studies.…”
Section: Responsible Editor: Yong Sik Okmentioning
confidence: 99%